Kecepatan Pelaporan Berbasis Sistem Informasi dan Pemeriksaan Manual Sesuai Standar Pelayanan Kementerian Kesehatan - Sa'adah Mujahidah; Melyana Nurul Widyawati (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to see and find out the differences in the speed of information-based reporting systems with manual inspection according to the Ministry of Health service standard procedures. This research is a quantitative research with quasy experimental research design using posttest only with control group design. The results showed that there was a difference in reporting time between reporting based on information systems with manual reporting on postpartum mothers with examinations according to the Ministry of Health standards with a p-value of 0,000 (<0.005). In conclusion, web-based information systems accelerate the reporting time of postpartum maternal health services compared to manual checks according to the Ministry of Health's service standards. Keywords: Postpartum, Speed, Information Systems, Time Reporting